PENGARUH KEMUDAHAN PENGGUNAAN, PERSEPSI KEGUNAAN, DAN COMPUTER SELF EFFICACY PADA MINAT PENGGUNAAN E-SPT - Bella Novindra, Ni Putu; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2017)
The purpose of this study was to test the effect of ease of use, perceived usefulness, and computer self efficacy in interest in the use of e-SPT. The population in this study is the taxpayer effectively on KPP Pratama Badung Utara with total 3076 Taxpayer. Based on the population, the sample in this study is 97 Taxpayers are calculated using the formula Slovin. The data collection technique used was accidental sampling in accordance with the criteria of sampling. Data analysis technique used is multiple linear regression. The result shows that the ease of use positively influence the interest of e-SPT usage, perception of usefulness positively influence the interest of e-SPT usage, and computer self efficacy positively influence the interest of e-SPT usage.
Keywords: Computer Self Efficacy, Using Interest.